2010
DOI: 10.1073/pnas.1001732107
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic account of value computation in the human brain

Abstract: To make decisions based on the value of different options, we often have to combine different sources of probabilistic evidence. For example, when shopping for strawberries on a fruit stand, one uses their color and size to infer-with some uncertainty-which strawberries taste best. Despite much progress in understanding the neural underpinnings of value-based decision making in humans, it remains unclear how the brain represents different sources of probabilistic evidence and how they are used to compute value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
108
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(129 citation statements)
references
References 47 publications
19
108
2
Order By: Relevance
“…This is in line with evidence suggesting that the ventral part of the medial PFC and OFC encodes the reward value of choice options Daw et al, 2006;Kim et al, 2006;Plassmann et al, 2008;Gasic et al, 2009;Hare et al, 2009;Kahnt et al, 2010Kahnt et al, , 2011Philiastides et al, 2010;Smith et al, 2010). Talmi and colleagues (2009) have demonstrated that activity in this region increases with rewards and is attenuated by the prospect of pain.…”
Section: Discussionsupporting
confidence: 66%
“…This is in line with evidence suggesting that the ventral part of the medial PFC and OFC encodes the reward value of choice options Daw et al, 2006;Kim et al, 2006;Plassmann et al, 2008;Gasic et al, 2009;Hare et al, 2009;Kahnt et al, 2010Kahnt et al, , 2011Philiastides et al, 2010;Smith et al, 2010). Talmi and colleagues (2009) have demonstrated that activity in this region increases with rewards and is attenuated by the prospect of pain.…”
Section: Discussionsupporting
confidence: 66%
“…A widespread network of brain regions is involved in this process, with the ventromedial prefrontal cortex being a value integration region (Basten et al, 2010;Philiastides et al, 2010), and parietal regions accumulating results of this integration (Basten et al, 2010;Gluth et al, 2012;Hunt et al, 2012). Because an accumulation mechanism implies a dynamic process which evolves over time, assessing the temporal dynamics of decision-making can be highly informative of the underlying neural process.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of studying single-trial activity has been highlighted by recent studies in value-based decision-making (Billeke et al, 2013;Gluth et al, 2013;Hunt et al, 2012;Philiastides et al, 2010). In particular, these studies have isolated readiness potentials in the EEG signal which reflect the emergence of value-based decisions (Gluth et al, 2013) or, in the case of MEG, have allowed tracking the information flow in brain regions linked to different stages of a decision (Hunt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The DDM has also been shown to provide highly accurate descriptions of accuracy and response times in domains such as memory retrieval and decision-making, where the stimuli are not explicitly stochastic (17,19,20,(22)(23)(24)(25)(26)(27)(28); this suggests that these decisions might be made using a similar process of random information accumulation and integration. To see why, consider the case of binary value-based choice.…”
mentioning
confidence: 99%
“…The standard drift-diffusion model (DDM), as well as closely related versions, such as the leaky competitive accumulator (LCA) model (3,4,9), have been highly successful in providing quantitative explanations of the psychometrics, chronometrics, and neurometrics of binary perceptual choice (2,(10)(11)(12)(13)(14)(15)(16), and more recently in binary value-based choice (17)(18)(19)(20). These models assume that decisions are made by accumulating stochastic information over time until the net evidence in favor of one option exceeds a prespecified threshold.…”
mentioning
confidence: 99%